Microneedles As a Delivery System for Gene Therapy - Chen, Wei; Li, Hui; Shi, De; Liu, Zhenguo; Yuan, Weien (Frontiers in Pharmacology, 2016)
Gene delivery systems can be divided to two major types: vector-based (either viral vector or non-viral vector) and physical delivery technologies. Many physical carriers, such as electroporation, gene gun, ultrasound start to be proved to have the potential to enable gene therapy. A relatively new physical delivery technology for gene delivery consists of microneedles (MNs), which has been studied in many fields and for many molecule types and indications. Microneedles can penetrate the stratum corneum, which is the main barrier for drug delivery through the skin with ease of administration and without significant pain. Many different kinds of MNs, such as metal MNs, coated MNs, dissolving MNs have turned out to be promising in gene delivery. In this review, we discussed the potential as well as the challenges of utilizing MNs to deliver nucleic acids for gene therapy. We also proposed that a combination of MNs and other gene delivery approaches may lead to a better delivery system for gene therapy.